Coronanomics: Implications of COVID-19 Pandemic in The Economy in Indonesia - Maghfuriyah, Alfi; Dewi, Nur Fitri; Antono, Zakia Maulida (Politeknik STMI Jakarta, 2024)
Coronanomics is the impact of the Covid-19 pandemic on the economy. The purpose of this study is to analyze the impact of the Covid-19 pandemic on the macro economy which includes several macro indicators, namely data on economic growth, inflation rates, interest rates, consumption, and investment in Indonesia as well as government policy responses in overcoming the Covid-19 pandemic. This study uses a literature study by taking data from several literatures that support the research process. This study uses quantitative data that is described qualitatively to analyze the impact on the macro economy. Data collection techniques used by listening and analyzing data by means of data reduction, data display, and an overview about the literature to be developed in this study. The results showed that the Indonesian economy in the third quarter of 2021 increased by 3.51% (yoy), although it slowed down compared to the previous quarter's achievements, household consumption grew by 1.03% (yoy). Investment growth slowed by 3.74% (yoy), supported by construction investment. The government's consumption performance was 0.66% (yoy), in line with the reallocation of spending to accelerate the national economic recovery program, including the handling of the Covid-19 delta. The inflation rate in October 2021 was 0.93%, a decrease compared to inflation in 2020 of 1.66%. The government's policy responses that have been carried out in order to overcome the Covid-19 pandemic are divided into two, namely through the Covid-19 Handling Policy and the National Economic Recovery Policy (PC-PEN).